English Education Freshmen’ Experience on Language Learning Anxiety - Suhardi, Sean Arthur Lawrence; Harida, Ratri (STKIP PGRI Ponorogo Press, 2024)
Language learning anxiety is a feeling of tension and fear of using English, especially in foreign language settings. Freshmen in the English education department tend to experience different types and levels of language learning anxiety. This descriptive quantitative study aims to find out and describe the type and level of language learning anxiety of the English education department freshmen using a survey. According to the findings, freshmen in the English education department experience more communication anxiety than test anxiety or fear of negative evaluation. The majority of students experience medium to high levels of anxiety for each type of language learning anxiety. Further research is needed to understand the reasons and ways to overcome language learning anxiety.